PERLUASAN ELEMEN EFEK DALAM KEGIATAN PASAR MODAL DALAM KAITANNYA DENGAN PERLINDUNGAN BAGI MASYARAKAT DARI KONTRAK INVESTASI YANG TIDAK TERDAFTAR DI BURSA - Yessi Serena Rangkuti; Bismar Nasution; O.K Saidin; Mahmul Siregar (Universitas Sumatera Utara, 2016)
ABSTRACT Popular contract investment in society tend to cause great loss to society for not being listed in the stock exchange and not provided with the consent of OJK, leading the difficulty of OJK to handle the situation. This research is conducted by seeing the investment contract in its relation to the capital market mechanism in providing decent protection to society, also, by seeing if investment contract is included in the limitation in capital market law regarding the definition of security itself and finally the elaboration of security term in capital market law to provide protection to the society. The method used in this research is normative law research conducted through the study of legislation and relevant legal material, assisted by collecting information from interviewee who has been involved in unlisted investment contract, and also by looking at cases happened in Indonesia and other country. The data is collected by library research and interview, and the analysis is conducted qualitatively. The results show that popular investment contract is not one listed in stock exchange, so that the enforced law regarding legal protection to the society in capital market law cannot guarantee the legal protection to the society investing their money in the unlisted investment contract in stock exchange and conducted without the consent of OJK. By looking at the fact that the practice of unlisted investment contract is very popular in the society, the Capital Market Law need to be renewed by elaborating the definition of securities by including investment contract as one of the securities. Keywords: Investment Contract, Elaboration of the term securities, Legal Protection